CAREGIVER RESILIENCE AND COMMUNITY SUPPORT SYSTEMS ON PREVENTING ELDER NEGLECT WITHIN FAMILIES AT IJEBU-NORTH LOCAL GOVERNMENT AREA, OGUN STATE, NIGERIA - Temple Tamuno-Opubo, Addah; Moses Adeyeye, Timileyin; Tuwleh, Levi; Oduyeru Oluwasegun, Joshua; David Nwankwo, Chinemerem (African Journal of Social and Behavioural Sciences, 2024)
In Nigerian society, the erosion of traditional values has significantly diminished the once- respected position and status of the older generation, leading to increased instances of elder neglect. Therefore, this paper investigated the role of caregiver resilience and community support systems in preventing elder neglect within families in the Ijebu-North Local Government Area of Ogun State, Nigeria. The participants included 211 (F = 135; mean age = 28.6) caregivers from various families within the Ijebu-North Local Government Area, Ogun State, Nigeria. Data were sourced through the Elder Assessment Instrument (EAI), Caregiver Resilience Scale (CRS) and Community Support System Questionnaire (CSSQ) and were analysed via multiple regression. The results indicated that the study population had an average prevalence rate of elder neglect of 51.70%. The results also revealed that caregiver resilience significantly predicted the prevention of elder neglect (β = .214, t = 3.148, p < .05). The results further revealed that community support systems alone did not significantly influence elder neglect prevention (β = .053, t = .778, p > .05). However, the combined effect of caregiver resilience and community support systems significantly influenced elder neglect prevention (F = 5.565, p < .05, R² = 0.051). The findings imply that interventions aimed at preventing elder neglect within families should prioritise enhancing caregiver resilience while also integrating community support systems, as the combination of these factors is more effective than focusing on either aspect alone. Furthermore, public awareness campaigns should be launched to educate families and communities about the importance of caregiver resilience and the available support systems, fostering a more supportive environment for both caregivers and elderly individuals.